Performance of waste cooking oil in asphalt binder modification - Wan Azahar, Wan Nur Aifa; Bujang, Mastura; Putra Jaya, Ramadhansyah; Hainin, Mohd Rosli; Ngadi, Norzita; Al Bakri Abdullah, Mohd Mustafa (Trans Tech Publications, Switzerland, 2016)
Oxidation, hydrolysis and polymerization process during frying activity has caused the alteration value of the waste cooking oil (WCO) properties which is acid value and water content. This parameter is recognized as the quality measurement of waste cooking oil that might be affecting the performance of WCO in binder modification. Therefore, the aim of this paper is to relate the quality of WCO by the determination of the WCO parameter with the performance of WCO in modified binder by physical and rheological binder testing. Based on the finding, the high and good quality of WCO is recorded in December sample with the lowest acid value (1.66 mL/g) and water content (0.01 ml). The high quality of WCO affected the good performance of rheological properties where the higher rutting resistance and temperature failure at 64 0C is achieved by the modified asphalt binder with the addition of WCO in December sample.